2012
DOI: 10.1111/j.1532-950x.2012.00972.x
|View full text |Cite
|
Sign up to set email alerts
|

Weight‐Based Volume of Injection Influences Cranial to Caudal Spread of Local Anesthetic Solution in Ultrasound‐Guided Transversus Abdominis Plane Blocks in Canine Cadavers

Abstract: In Beagle cadavers, the volume of injected local anesthetic solution significantly affects cranial to caudal spread within the TAP during ultrasound-guided TAP blocks. The volume of local anesthetic injected could potentially be used to augment the spread of analgesic coverage for a given surgical procedure in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 11 publications
2
27
0
1
Order By: Relevance
“…, Bruggink et al . ). The three muscle layers were identified: external oblique, internal oblique and transversus abdominis .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…, Bruggink et al . ). The three muscle layers were identified: external oblique, internal oblique and transversus abdominis .…”
Section: Methodsmentioning
confidence: 97%
“…Bruggink et al . () found that the volume of injection correlated with dermatomal spread when assessed via dissection in dog cadavers, but doubling the volume from 0·5 to 1 mL/kg did not result in doubling the number of nerve roots stained. A subcostal injection was evaluated in dog cadavers and this technique allowed the blockade of nerves up to T9 in some cadavers when a mean volume of 0·76 mL/kg of 1% methylene blue was used (Drozdzynska et al .…”
Section: Introductionmentioning
confidence: 96%
“…This locoregional anaesthetic technique consists in the injection of a volume of local anaesthetic into the TAP, with the aim to obtain its distribution over the thoracolumbar nerve branches located within this fascial plane. This technique is considered promissory to produce analgesia for surgical procedures performing on the abdominal wall such as laparoscopic surgery, laparotomies and radicals or partial mastectomies in dogs (Schroeder et al., ; Bruggink et al., ; and Portela et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In veterinary anaesthesia, the posterior approach for US-guided TAP block was described in dog 41 cadavers (Schroeder et al 2011;Bruggink et al 2012 College, London.…”
mentioning
confidence: 99%